Islamic bank deposits during COVID-19 pandemic : a spatial finance approach - Wicaksono, Ahmad Tibrizi Soni (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to determine factors affecting deposits in banks during COVID-19 pandemic by employing a spatial finance approach on a sample of Islamic Rural Banks in the Indonesian archipelago. The results showed that the COVID-19 pandemic, capital financing, and bank asset had a spatial influence on bank deposits. Specifically, while COVID-19 pandemic reduces bank deposits, capital financing and bank assets increase these. Using Spatial Lag Model and Local Indicator of Spatial Autocorrelation through Spatial Rate Analysis, the study further found that there is a potential spillover effect in certain provinces based on the bank deposit relationship with COVID-19, financing and bank assets. This implies that the three factors tend to spatially affect the socio-economic activities of the neighboring areas of certain provinces. This study may shed some light for the government in determining post-COVID-19 economic recovery policies using a geographical approach in providing information on financial interactions between regions.